2018
DOI: 10.1128/iai.00550-17
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic Escherichia coli Adhesin-Toxoid Multiepitope Fusion Antigen CFA/I/II/IV-3xSTa N12S -mnLT G192G/L211A -Derived Antibodies Inhibit Adherence of Seven Adhesins, Neutralize Enterotoxicity of LT and STa Toxins, and Protect Piglets against Diarrhea

Abstract: Enterotoxigenic (ETEC) strains are a leading cause of children's diarrhea and travelers' diarrhea. Vaccines inducing antibodies to broadly inhibit bacterial adherence and to neutralize toxin enterotoxicity are expected to be effective against ETEC-associated diarrhea. 6×His-tagged adhesin-toxoid fusion proteins were shown to induce neutralizing antibodies to several adhesins and LT and STa toxins (X. Ruan, D. A. Sack, W. Zhang, PLoS One 10:e0121623, 2015, https://doi.org/10.1371/journal.pone.0121623). However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Based on PCR analysis, we observed fewer Lactobacillus and more Enterobacteriaceae in TGEV-infected pigs. Among Enterobacteriaceae family, Escherichia coli is the most common cause of diarrhea in pigs and piglets [22][23][24]. Research has shown that animals with signs of intestinal disease have far greater numbers of Enterobacteriaceae than do healthy individuals, and that the Enterobacteriaceae are linked to intestinal disorders [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Based on PCR analysis, we observed fewer Lactobacillus and more Enterobacteriaceae in TGEV-infected pigs. Among Enterobacteriaceae family, Escherichia coli is the most common cause of diarrhea in pigs and piglets [22][23][24]. Research has shown that animals with signs of intestinal disease have far greater numbers of Enterobacteriaceae than do healthy individuals, and that the Enterobacteriaceae are linked to intestinal disorders [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse serum anti-CFA adhesin and anti-LT IgG antibody titers were measured in ELISAs as previously described. [23][24][25] Briefly, wells of 2HB plates (Thermo Scientific, Rochester, NY) coated with 100 ng of heat-extracted fimbriae (CFA/I, CS1, CS2, CS3, CS4, CS5), recombinant CS6 subunit protein CssA, or cholera toxin (CT; Sigma, St. Louis, MO) were incubated with two-fold diluted mouse serum samples (from 1:200 to 1:51200) for 1h at 37°C. Horseradish peroxidase (HRP)-conjugated goat antimouse IgG (1:3000; Bethyl Laboratories, Montgomery, TX) and 3,3ʹ,5,5ʹ-tetramethylbenzidine (TMB) Microwell Peroxidase Substrate System (KPL, Gaithersburg, MD) were used to measure optical density (OD 650 ).…”
Section: Mouse Anti-cfa and Anti-lt Igg Antibody Titrationmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Recent studies suggested that dmLT adjuvant might have positive immunoregulatory properties when given parenterally with vaccine antigens. 22,23 The potential impact of adding dmLT to a parenteral subunit ETEC vaccine, however, has not been fully investigated. In this study, we subcutaneously (SC) immunized mice with ETEC adhesin MEFA (multiepitope fusion antigen) CFA/I/II/IV, a leading and novel subunit ETEC vaccine candidate, and examined dmLT adjuvant activity in up-regulating antibody responses to the seven ETEC adhesin antigens included in the vaccine construct, CFA/I, CFA/II (CS1, CS2, CS3) and CFA/IV (CS4, CS5, CS6).…”
Section: Introductionmentioning
confidence: 99%
“…By mimicking epitope native antigenicity and presenting multiple heterologous neutralizing epitopes at a backbone immunogen, MEFA vaccinology allows a single immunogen (protein) to carry multiple antigenic elements (epitopes or peptides) from various virulence determinants for broad immunogenicity, thus allowing the development of a broadly immunogenic multivalent vaccine. With this MEFA technology, we have successfully generated ETEC fimbria MEFAs for broadly protective immunity against seven or nine human ETEC virulence determinants (colonization factor antigen [CFA] adhesins) (9-11) and adhesin-toxoid MEFAs for antibodies not only inhibiting adherence of seven human ETEC adhesins and neutralizing LT and STa enterotoxicity but also protecting against ETEC diarrhea in a pig challenge model (12,13). These MEFAs have become leading antigens for human ETEC subunit vaccines against children's diarrhea and traveler's diarrhea.…”
mentioning
confidence: 99%